Penerapan media komik matematika terhadap peningkatan pemahaman konsep perkalian dan pembagian bilangan cacah di sekolah dasar - Dedi Kurniawan; Karlimah Karlimah; Yusuf Suryana (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2015)
The background of the reaseach is difficulty student to understanding about multiplication and division at whole number and the use of instructional media that matches the stage of development for elementary school student. Therefore selected math comic in learning multiplication and division of whole numbers for elementary school students, because comics are mostly readed by elementary school students. Thus the formulation of the problem is how comics can be used as a media of learning mathematics, and how it affects the understanding of multiplication and division concept in whole numbers to elementary school students. General research purpose was to describe the mathematical model of the comic can be used as media of mathematics learning, and knowing its impact on understanding of multiplication and division concept in whole numbers to elementary school students. The research is quasi experimental design type Nonequivalent Control Group with purposive sampling. Data collection techniques used are questionnaires and tests. To analyze quantitative data, researcher use Microsoft Excel 2010 and SPSS 16.0. The result show that math comic media give positive influence in the understanding of multiplication and division concept in whole numbers other than conventional learning.